Clifford Geertz: A career - Bošković Aleksandar (Glasnik Etnografskog Instituta SANU, 2007)
The paper presents some concepts of the recently deceased American anthropologist Clifford Geertz, putting them into the specific context of his rich and interesting career, influences that he had, as well as some reactions to his ideas. A particular attention is placed upon the concept of culture, as the key concept in the 20th century American anthropology.